FY2018 Eswatini Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2019)
The Country Opinion Survey in Eswatini (Swaziland) assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Eswatini (Swaziland) perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Eswatini (Swaziland) on 1) their views regarding the general environment in Eswatini (Swaziland); 2) their overall attitudes toward the WBG in Eswatini (Swaziland); 3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Eswatini (Swaziland); and 4) their perceptions of the WBG’s future role in Eswatini (Swaziland).